Effectiveness of Microneedling Combined with Topical Triamcinolone Acetonide versus Microneedling Alone in Treatment of Alopecia Areata - Riaz, Novera; Arfan ul Bari; Kakar, Asmat Ullah; Zaidi, Syeda Naveen; Fatima, Attiya; Waqar, Shazia (Indus Journal of Bioscience Research, 2025)
Background: Alopecia areata (AA) is a prevalent, inflammatory, non-scarring form of hair loss. The clinical presentation of AA exhibits considerable variability. Although numerous therapies are available for managing this condition, these treatment modalities yield inconsistent clinical outcomes, and there are currently no treatments that reliably induce or sustain remission. Methods: A comparative study was conducted at the Pakistan Emirates Military Hospital’s Department of Dermatology from June 2024 to November 2024. The study included 40 patients aged 16 to 50 with localized alopecia areata (AA) who had not received treatment in the prior three months. Exclusions were severe AA forms, recent AA treatment, known allergies to medications, and active infections. Participants provided informed consent and were divided into two groups: Group A received microneedling combined with topical triamcinolone acetonide (10 mg/ml), and Group B received microneedling alone. Baseline and follow-up assessments included digital photography and Severity of Alopecia Tool (SALT) scoring. Data were analysed using IBM-SPSS 21.0 with statistical significance set at p ≤ 0.05. Results: The age distribution showed a mean ± SD of 32.6 ± 9.7 years for the MN + TrA group and 33.5 ± 10.4 years for the MN alone group, with a p-value of 0.09. The MN + TrA group comprised 60.0% males and 40.0% females, while the MN alone group had 25.0% males and 75.0% females (p = 0.12). Baseline SALT scores were comparable (p = 0.14). MN + TrA yielded significantly better responses, with 60.0% achieving complete recovery versus 5.0% in MN alone (p = 0.001). Side effects were minimal; irritation occurred in 5.0% of MN + TrA participants, with no significant differences in redness or scaling (p = 0.13). MN + TrA was more effective and well-tolerated than MN alone. Conclusion: Microneedling combined with topical triamcinolone acetonide are safe and effective therapeutic options for localized AA.